Determination of Yield and Some Fruit Quality Characteristics of the Festival and Camarosa Strawberry Cultivars Grown in Aydın/Sultanhisar Conditions - Seda Erdoğan Bayram (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the yield and various quality characteristics of two different strawberry cultivars (Fragaria x ananassa var. Festival and Camarosa), grown in the ecological conditions of Sultanhisar, Aydın, Turkey. The study was conducted over two years, in ten randomly selected open grown plantations for each of the two cultivars. When the fruits reached harvest maturity, they were harvested and their yield values, mean fruit weight, fruit diameter, fruit length, fruit firmness, colour, pH, titrable acidity, water-soluble dry matter, vitamin C content, total antioxidant capacity and total phenolics were determined. According to the results obtained, yield values fell in the second year of the study, but mean fruit weight, diameter and length increased. Similarly, the fruit firmness of both varieties was considerably greater in the second year, and these differences between the years were found to be statistically significant. While the highest antioxidant capacity and phenolic content were obtained from the Festival cultivar, the highest vitamin C content was found in the Camarosa cultivar. The changes of total antioxidant capacity and the amount of total phenolics according to years of both varieties were found to be statistically significant.